A new species of Astacilla (Crustacea: Isopoda: Valvifera) from the Le Danois Bank (N Spain, NE Atlantic), living on Placogorgia sp. (Cnidaria: Octocorallia) with notes on the cnidarian host. (June 2019) - Taboada, Sergi; Altuna, Álvaro; Sánchez, Francisco; Junoy, Juan
Abstract: Located in the Cantabrian Sea (NE Atlantic), El Cachucho is the largest offshore Marine Protected Area (MPA) in Spain. One of the most abundant keystone megafauna species occurring in this MPA is a yellow gorgonian of genus Placogorgia Wright and Studer (1889), occurring in relatively high densities in steep slopes with rocky outcrops at depths ranging 500–1200 m. Here, we describe a new species of isopod, Astacilla andresmeixidei sp. nov., living in association with a specimen of a yellow gorgonian collected at 525 m depth. Females of the new species are characterised by a trapezoidal pereonite 4 with a middorsal bifurcate tubercle on posterior margin; males have a rectangular pereonite 4 with small tubercles irregularly distributed and pereonite 3 with a midventral process. The new species is distinguished from the most morphologically similar species Astacilla gorgonophila Monod (1925) by its dorsal sculpture, having a shorter antenna 2 with a flagellum of three articles plus a claw, and also by its geographic and bathymetric distribution. Phylogenetic analysis using the mitochondrial marker COI confirmed that the new isopod is a member of the family Arcturidae and placed it in a clade, recovered with low support, including other species of the genus Astacilla Cordiner, 1793. As with other previously described arcturids, we suggest that A. andresmeixidei sp. nov. is a commensal of the gorgonian using its branches to reach higher in the water column and thus increase its chances to get more particulate organic matter. Our morphological analyses on the gorgonian host, suggest that it belongs to the genus Placogorgia although in our phylogenetic results using the nuclear marker msh1 the gorgonian shows affinities with the genus Paramuricea Kölliker (1865). This taxonomic inconsistency is discussed. Highlights: A new deep-sea Astacilla species is described from the Cantabrian Sea (NE Atlantic). The new isopod was found in association with a keystone gorgonian ( Placogorgia sp.) We provide morphological and phylogenetic evidence for the isopod and the gorgonian.